17 PESAN DAKWAH RIKO THE SERIES - Afifi, Mohammad; As-Shobri, Ach. Faizal Umam (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2023)
The cultivation of character values, especially those of a religious and social ethical nature, which are part of the preaching activities, should begin from an early age. The strategy of conveying and instilling these values can be done in various ways, one of which is by utilizing children's animated media that tends to be liked by children. In this research, the researcher explores the children's animated series